Ipsilateral Lower Ureteroureterostomy for The Management of Ureteric Duplication Anomalies in Children: A Prospective Study - Salama, Amr; Youssif , Mohamed; Fahmy , Ahmed; Badawy , Haytham; Fahmy , Ziad; Dawood , Waleed (Iranian Journal of Pediatric Surgery, 2025)
Introduction: Congenital Duplex anomaly of the ureters is a challenging clinical disorder, which is described in approximately 1 % of children with higher prevalence in girls. It arises from abnormal location of ureteric bud from wolffian duct during embryogenesis. A condition that can be diagnosed antenatally. The upper moiety usually ends with either a ureterocele or an ectopic ureter. Management options include expectant conservative management, transurethral ureterocele incision (TUI), ipsilateral ureteroureterostomy, upper pole hemi nephrectomy and total reconstruction with common sheath reimplantation. Evaluation of the short-term effect of lower ipsilateral ureteroureterostomy procedure for the management of ureteric duplication anomalies in children. Material and Methods: A prospective study including thirty-two children with complete duplex anomalies in which the ipsilateral upper moiety ureter is affected from March 2023 to March 2024 were included in the study. All patients underwent open ipsilateral lower ureteroureterostomy. Results: Thirty-two children (21 male, 11 female patients) underwent ipsilateral Ureteroureterostomy, 75% of the patients had ureterocele and the remaining had ectopic ureter. Mean age was 20.6 months. Urinary tract Infection was the most common presenting symptom in 59.4%, Other presentations include antenatal hydronephrosis in 28.1% and incontinence in 12.5%. Median follow up was 10.43 months (IQR:8.1-14.3). The percentage of children experiencing adverse events is 15.6%, in the form of post-operative UTI in 4 cases (12.5 %) and one case, in which the operator could not pass a JJ stent intraoperatively and performed subsequent reoperation. Conclusion: Ipsilateral ureteroureterostomy has a low risk of surgical morbidities and low rate of complementary redo operation in children. We recommend performing it in duplex anomalies whose primary pathology is an ectopic ureter.